Toward a Monetary Union in the East African Community : Asymmetric Shocks, Exchange Rates, and Risk-Sharing Mechanisms - Drummond, Paulo; Aisen, Ari.; Alper, Emre.; Fuli, Ejona (Washington, D.C. : International Monetary Fund, 2015)
This paper examines how susceptible East African Community (EAC) economies are to asymmetric shocks, assesses the value of the exchange rate as a shock absorber for these countries, and reviews adjustment mechanisms that would help ensure a successful experience under a common currency. The report draws on analysis of recent experiences and examines likely future changes in the EAC economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet